2019
DOI: 10.1186/s42523-019-0004-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of the macroalgae Asparagopsis taxiformis on methane production and rumen microbiome assemblage

Abstract: Background: Recent studies using batch-fermentation suggest that the red macroalgae Asparagopsis taxiformis has the potential to reduce methane (CH 4) production from beef cattle by up to~99% when added to Rhodes grass hay; a common feed in the Australian beef industry. These experiments have shown significant reductions in CH 4 without compromising other fermentation parameters (i.e. volatile fatty acid production) with A. taxiformis organic matter (OM) inclusion rates of up to 5%. In the study presented here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
145
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(171 citation statements)
references
References 53 publications
18
145
5
3
Order By: Relevance
“…Expanding other markets-such as the use of certain seaweed strains in livestock feed, where inclusion in cow diets Hypoxia is considered dissolved oxygen levels less than 2 mgL À1 . Acidification is represented here by estimated aragonite saturation (U) less than 3.0. may significantly (75%-99%) reduce ruminant methane production [48][49][50]-as well as offshore production for biofuel [16], could further accelerate economies of scale. That said, climate change and increases in CO 2 will challenge some farmed seaweed species' growth and survival [3,14], limiting the upper bounds of sequestration while potentially promoting growth in others [51,52].…”
Section: Resultsmentioning
confidence: 99%
“…Expanding other markets-such as the use of certain seaweed strains in livestock feed, where inclusion in cow diets Hypoxia is considered dissolved oxygen levels less than 2 mgL À1 . Acidification is represented here by estimated aragonite saturation (U) less than 3.0. may significantly (75%-99%) reduce ruminant methane production [48][49][50]-as well as offshore production for biofuel [16], could further accelerate economies of scale. That said, climate change and increases in CO 2 will challenge some farmed seaweed species' growth and survival [3,14], limiting the upper bounds of sequestration while potentially promoting growth in others [51,52].…”
Section: Resultsmentioning
confidence: 99%
“…Feeding ruminants the red seaweed Asparagopsis taxiformis quickly (e.g. 3 days) changed the rumen microbial composition leading to drastic reduction of methanogenic Archaea and as a result led to reductions in enteric methane emissions [67,68]. This was the result of supplementing the diets of the ruminants (ovine and bovine) with up to 5% A. taxiformis which produces and accumulates halogenated compounds including the anti-methanogenic bromoform [69].…”
Section: Discussionmentioning
confidence: 99%
“…Achievable methods for CH 4 emission reductions have already been identified in a variety of sectors, some of them more developed and others still in the research stage. Within agriculture, preliminary research has shown how red algae and other dietary supplements can reduce methane emissions from cattle and sheep by as much as 95% (e.g., Li et al, ; Roque et al, ). Considerably more work is needed, however, to determine whether such supplements can be scaled industrywide and to confirm no change to nutrition or taste.…”
Section: The Role Of Atmospheric Ch4 In Achieving Global Climate Targetsmentioning
confidence: 99%